2016
DOI: 10.1371/journal.pone.0154072
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of ABA Effects on Ethylene Biosynthesis and Signaling during Tomato Fruit Ripening

Abstract: ABA has been widely acknowledged to regulate ethylene biosynthesis and signaling during fruit ripening, but the molecular mechanism underlying the interaction between these two hormones are largely unexplored. In the present study, exogenous ABA treatment obviously promoted fruit ripening as well as ethylene emission, whereas NDGA (Nordihydroguaiaretic acid, an inhibitor of ABA biosynthesis) application showed the opposite biological effects. Combined RNA-seq with time-course RT-PCR analysis, our study not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
97
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 131 publications
(109 citation statements)
references
References 100 publications
11
97
0
1
Order By: Relevance
“…In agreement with previous studies, our results showed that application of ABA accelerated persimmon fruit ripening, concomitant with promoting ethylene synthesis and loss of firmness (Figure 1B,D) [38,40,76]. Additionally, exogenous ABA was associated with enhanced transcriptional levels of DkLOX3 during fruit ripening (Figure 5B).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In agreement with previous studies, our results showed that application of ABA accelerated persimmon fruit ripening, concomitant with promoting ethylene synthesis and loss of firmness (Figure 1B,D) [38,40,76]. Additionally, exogenous ABA was associated with enhanced transcriptional levels of DkLOX3 during fruit ripening (Figure 5B).…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, exogenous ABA was associated with enhanced transcriptional levels of DkLOX3 during fruit ripening (Figure 5B). Some evidence has suggested that ethylene and ABA play fairly important roles in the control of fruit ripening [38,40,73,77]. In tomato and peach fruits, ABA promotes ripening by inducing ethylene biosynthesis through the up-regulation of ethylene biosynthesis genes [76].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is unclear how ETR2 is having this effect. It is known that stress and application of ABA can affect the transcript levels of the ethylene receptors in various plant species (Zhao and Schaller, 2004;Martín-Rodríguez et al, 2011;Mou et al, 2016). We were therefore curious to know if application of ABA altered the transcript levels of the five ethylene receptors, and whether loss of either ETR1 or ETR2 affected ABA-induced changes in the other receptors.…”
Section: Etr1 Ein4 and Etr2 Affect Responsiveness To Abamentioning
confidence: 99%
“…RNA-Seq also allows quantification of the relative alterations of each transcript during defined developmental stages or under specific treatment conditions in plants. For example, RNA-Seq was used to study the regulation of auxin and gibberellin (GA), and the effect of abscisic acid (ABA) on fruit ripening (Mou et al, 2016;Tang et al, 2015;Li et al, 2016;Ye et al, 2015). In this study, RNA-Seq was used to study the transcriptome changes under 1-MCP treatment to understand the effect of 1-MCP on tomato fruit ripening at the genomic level.…”
Section: Introductionmentioning
confidence: 99%